Does Treatment of Preoperative Asymptomatic Bacteriuria Reduce the Rate of Postoperative Prosthetic Joint or Surgical Site Infection in Elective Joint Arthroplasty? A Systematic Review - Sathanandan, Krishanthi; Partridge, Judith; Hemsley, Carolyn; Shah, Zameer; Dhesi, Jugdeep (International Journal of Orthopedics and Rehabilitation, 2018)
Introduction: Inconsistent guidelines for management of preoperative asymptomatic bacteriuria (ASB) prior to elective joint arthroplasty leads to practice variance, surgical delays and antimicrobial overuse. This systematic review examined whether: 1) preoperative ASB in patients awaiting elective arthroplasty was associated with increased rates of postoperative prosthetic joint (PJI) and surgical site infection (SSI) 2) treatment of ASB modifies these rates. Methods: A textual narrative synthesis was performed of randomised control, quasiexperimental and observational studies (identified through MEDLINE, EMBASE, HMIC and grey literature resources), which included patients with ASB and an outcome measure of rate of PJI/SSI. Significant study heterogeneity precluded meta-analysis. Results: Eleven studies (comprising a total of 31857 patients) were included: one randomised control, three quasiexperimental, and seven observational studies. Ten studies involved a control group to address whether ASB was associated with PJI/SSI. Eight out of these ten studies found no association between ASB and PJI/SSI; two studies found an association. Only four out of 239 cases across all studies grew identical pathogens in wound and urine cultures. One study only included patients with ASB and focused on whether treatment of ASB reduced PJI incidence. Two of the former ten studies also explored this. No studies reported that treatment of ASB reduced rates of PJI/SSI. Conclusions: Treatment of ASB prior to joint arthroplasty does not reduce rates of PJI/SSI. Within the current climate of antibiotic stewardship and financial healthcare pressures, this review suggests that preoperative urine cultures should not be routinely sent in asymptomatic patients prior to elective joint arthroplasty.